Clinical updates in adult acute lymphoblastic leukemia. (March 2016) - Ustwani, Omar Al; Gupta, Neha; Bakhribah, Hatoon; Griffiths, Elizabeth; Wang, Eunice; Wetzler, Meir
Highlights: Recent evidence shows that "Philadelphia-like" ALL demonstrates unfavorable outcome due to various kinase-activating mutations. Monitoring minimal residual disease is becoming a powerful tool in management of ALL. Recombinant genes for chimeric antigen receptors are introduced into autologous T cells to redirect immune response against leukemic cells. Abstract: Acute lymphoblastic leukemia (ALL) is a clonal disease characterized by B or T lineage. Here we cover the clinical manifestations, pathophysiology and therapy for ALL. Additionally, we will discuss the evidence for minimal residual disease assessment, novel molecular targets and newly developed targeted therapies. The separation of ALL into Philadelphia chromosome positive and recently into Philadelphia-like disease represents the most exciting developments in this disease. Finally, the advent of new immunotherapeutic approaches led us to predict that in few years, ALL therapy might be based heavily on non-chemotherapeutic approaches.